SHARIA-BASED GOLD SALES STRATEGY FOR PROFIT OPTIMIZATION: A CASE STUDY OF SINAR JAYA GOLD SHOP, BOGOR - Jamil, Abdul; Wahdan; Widodo, Tri; Aniyatussaidah; Muinah, Siti (UTSAHA: Journal of Entrepreneurship, 2024)
The integration of modern marketing practices with Sharia compliance presents a critical challenge for traditional gold retailers in Indonesia. Despite growing scholarly attention to Islamic finance, empirical research examining how micro-scale gold retailers operationalize Sharia-based sales strategies remains limited. This study analyzes gold sales strategies and profit optimization within the framework of Sharia economic law at Sinar Jaya Gold Shop, Cigudeg, Bogor Regency. The research addresses three objectives: identifying sales strategies implemented, examining profit enhancement efforts, and evaluating conformity with Islamic legal principles. Employing a qualitative design, data were collected through field observation, in-depth interviews with the store manager, employees, and academic experts in Islamic economics, and documentation review. Findings reveal that the shop adopts a hybrid marketing model combining direct selling, educational brochure distribution at religious venues, and digital engagement through WhatsApp and Facebook Marketplace. Profit enhancement is pursued through product diversification, transparent daily pricing aligned with global gold indices, and strict cash-based transactions ensuring immediate possession transfer. The study concludes that profit generation in gold trading is permissible under Sharia economic law when conducted within ethical boundaries, particularly through compliance with mutual consent, price transparency, and avoidance of riba and gharar. This research contributes empirical evidence demonstrating how traditional retail businesses can align profit-oriented strategies with Sharia-based standards, offering practical insights for micro-entrepreneurs and policymakers promoting sustainable Islamic business practices.